Application of stiffness rings for improvement of operating reliability of the tank with shape imperfections - Lukianchenko, O. O. (КНУБА, 2020)
An efficiency of using of two stiffness rings for improvement of operating reliability of the tank with real shape imperfection at the action of combination load was evaluated. The computer model of the tank was constructed in the form of the thin cylindrical shell by of the program complex of finite element analysis. The tank stability problem under separate and joint action of surface pressure and axial compression was solved by the Lancosh method in linear formulation and as a nonlinear static problem by the Newton-Raphson method. The region of the tank failure-free work, which has the graphical presentation, confirmed the improvement of the tank wall stability due to the use of stiffness rings, especially in the area of surface pressure action.
Застосування кілець жорсткості для покращення експлуатаційної надійності резервуара з недосконалостями форми
Применение колец жесткости для улучшения эксплуатационной надежности резервуара с несовершенствами формы
Keywords: finite element method; operating reliability; stability; tank; failure-free region; thin-walled shell; shape imperfection; combined load; stiffness ring; метод скінченних елементів; надійність експлуатації; стійкість; резервуар; область безвідмовної роботи; тонкостінна оболонка; недосконалість форми; комбіноване навантаження; кільце жорсткості; 539.3